Determination of sunset yellow, allura red, and fast green using a novel magnetic nanoadsorbent modified with Elaeagnus angustifolia based on magnetic solid-phase extraction by HPLC - Tülay Oymak; Emrah Dural (Universidade de São Paulo, 2023)
Abstract Sunset yellow (SY), allura red (AR) and fast green (FG) are frequently used in commercial food products, although they are considered to be hazardous to public health due to their toxic efficacy and high exposure risk potency. In this study, a new, rapid, and reliable method based on a magnetic solid-phase extraction (MSPE) was developed for the simultaneous determination of SY, AR, and FG. Fe3O4 modified with Elaeagnus angustifolia was used for the first time as an adsorbent (Fe3O4-EA) in MSPE. It was characterized with scanning electron microscopy, Brunauer Emmet Teller surface area analysis and X-ray diffraction. MSPE parameters were optimized in terms of pH, adsorption, and elution time and elution volume. High-performance liquid chromatography was used for dye quantitation. Analytical separation was performed by applying ammonium acetate buffer, acetonitrile, and methanol as the mobile phase to a C18 reverse-phase analytical column. Intraday and inter-day repeatability of the method performed at the concentration of 0.2, 1.0 and 2.0 µg/mL exhibited <8.1% RSD (n=3). The limit of detection values was between 0.05-0.1 µg/mL. The adsorption data of SY, AR and FG on Fe3O4-EA were fitted with the Langmuir model with qmax values of 45.0, 70.4 and 73.0 mg/g, respectively.